2017
DOI: 10.1149/2.0711707jes
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Design for Voltage Driven Tracer Incorporation and Diffusion Studies on Oxide Thin Film Electrodes

Abstract: The effect of an applied overpotential on oxygen isotope incorporation and diffusion in oxide thin film electrodes is investigated by a novel experimental approach. A special electrode geometry leads to in-plane electron flow, perpendicular oxide ion flow and a well-defined laterally varying driving force. This design allows one to obtain a series of tracer depth profiles induced by a range of overpotentials on one and the same thin film. The approach was applied to La 0.8 Sr 0.2 MnO 3 (LSM) thin films deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The requirement for this condition is that the whole region of the electrode surface should be electrochemically active so that the ionic current is not drained solely through the near-WE region; this condition is met when the electronic current is far higher than the ionic current ( I elec ≫ I ion ). Huber et al showed that LSM had the appropriate electronic and ionic properties which satisfied such a condition. We have also confirmed the presence of a linear potential variation across the film surface, by in situ core-level photoemission measurements of LSM under polarization (Figures S2 and S3 in the Supporting Information).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The requirement for this condition is that the whole region of the electrode surface should be electrochemically active so that the ionic current is not drained solely through the near-WE region; this condition is met when the electronic current is far higher than the ionic current ( I elec ≫ I ion ). Huber et al showed that LSM had the appropriate electronic and ionic properties which satisfied such a condition. We have also confirmed the presence of a linear potential variation across the film surface, by in situ core-level photoemission measurements of LSM under polarization (Figures S2 and S3 in the Supporting Information).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The setup for the simultaneous probing of a range of polarization (Figure 1) is based on the recent design by Huber et al 57 The sample bias is applied to a Pt contact sputtered onto the electrode film, while the counter electrode (CE), the porous Pt layer on the back side of the YSZ electrolyte, is connected to ground. In contrast to a traditional CE, this model electrode is in electrical contact with a stripe of Pt on the working electrode (WE) side of the electrolyte crystal, connecting it to the thin-film electrode.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, two of these techniques could be used in combination 47,50 . More recently, the effect of applying an overpotential to the oxygen isotope exchange and diffusion in oxide thin film electrodes has been investigated 51 . An oxygen stoichiometry re-equilibration method under reducing conditions using solid electrolyte coulometry 52 or a thermogravimetric relaxation technique 53 has also been proposed.…”
Section: Introductionmentioning
confidence: 99%